Hybrid Biomaterial with Conjugated Growth Factors and Mesenchymal Stem Cells for Ectopic Bone Formation - Yuan, Xue (Tissue Eng Part A, 2016)
Bone is a highly vascularized tissue and efficient bone regeneration requires neovascularization, especially for critical-sized bone defects. We developed a novel hybrid biomaterial comprising nanocalcium sulfate (nCS) and fibrin hydrogel to deliver mesenchymal stem cells (MSCs) and angiogenic factors, vascular endothelial growth factor (VEGF) and fibroblast growth factor 9 (FGF9), to promote neovascularization and bone formation. MSC and growth factor(s)-loaded scaffolds were implanted subcutaneously into mice to examine their angiogenic and osteogenic potential. Micro CT, alkaline phosphatase activity assay, and histological analysis were used to evaluate bone formation, while immunohistochemistry was employed to assess neovessel formation. The presence of fibrin preserved the nCS scaffold structure and promoted de novo bone formation. In addition, the presence of bone morphogenic protein 2-expressing MSC in nCS and fibrin hydrogels improved bone regeneration significantly. While FGF9 alone had no significant effect, the combination FGF9 and VEGF conjugated in fibrin enhanced neovascularization and bone formation more than 4-fold compared to nCS with MSC. Overall, our results suggested that the combination of nCS (to support bone formation) with a fibrin-based VEGF/FGF9 release system (support vascular formation) is an innovative and effective strategy that significantly enhanced ectopic bone formation in vivo.